Integrated land systems for sustainable food production and biodiversity conservation in the semi-arid to moist tropics: Stakeholder perspectives from Andhra Pradesh, India - Berger, Iris; Bhan, Manan; Bhangaonkar, Rekha; Chaudhary, Abhishek; Mallapu, Gopinath R.; Nair, Tanaya; Ramireddy, Eswarayya; Raj, Rengalakshmi; Ramprasad, Vijay; Sankararaman, Vishnupriya; Singh, Vartika; Hareesha, A. S.; et al. (Frontiers Media, 2025)
Land systems must urgently be transformed for social and environmental sustainability, which necessitates a better integration of food system and biodiversity governance. This is particularly pronounced in the south-Indian state Andhra Pradesh, where one of the largest agroecological transitions globally, namely Zero Budget Natural Farming (ZBNF), is currently underway, but involvement of conservation scientists and practitioners has been minimal and policy spheres are disjunct. Here, we report the results of a multi-stakeholder exercise to ascertain the multi-scalar and multi-institutional transformations needed for Andhra Pradesh ‘s landscapes to deliver both food and biodiversity targets. To achieve a vision of an equitable and sustainable food system and of multifunctional and nature-positive land systems, we advocate for an end to harmful subsidies, improvements in infrastructures and social organisations, dietary shifts, and creation of both supporting financial structures and sustainable and transparent value chains. We stress that approaches should be participatory and link across policy domains and scales, bridging bottom-up and top-down perspectives, and with spatial planning critical to balancing land system objectives. Specifically, we stress that the ZBNF transition needs to be better aligned with state-level conservation strategies to maximise biodiversity benefits. Top priority knowledge needs include quantifying the multidimensional performance and scaling-potential of agroecological systems, the effectiveness of different conservation interventions, and how different land system objectives trade off against each other. Our work highlights a lack of data and capacity sharing, which can be addressed through intersectoral partnerships and collaborative programmes to create effective, research-based policies and land management strategies.